When A+B < A: Cognitive Bias in Experts’ Judgment of Environmental Impact - Holmgren, Mattias; Kabanshi, Alan; Marsh, John E.; Sörqvist, Patrik (Frontiers in Psychology, 2018)
When ‘environmentally friendly’ items are added to a set of conventional items, people report that the total set will have a lower environmental impact even though the actual impact increases. One hypothesis is that this “negative footprint illusion” arises because people, who are susceptible to the illusion, lack necessary knowledge of the item’s actual environmental impact, perhaps coupled with a lack of mathematical skills. The study reported here addressed this hypothesis by recruiting participants (‘experts’) from a master’s program in energy systems, who thus have bachelor degrees in energy-related fields including academic training in mathematics. They were asked to estimate the number of trees needed to compensate for the environmental burden of two sets of buildings: One set of 150 buildings with conventional energy ratings and one set including the same 150 buildings but also 50 ‘green’ (energy-efficient) buildings. The experts reported that less trees were needed to compensate for the set with 150 conventional and 50 ‘green’ buildings compared to the set with only the 150 conventional buildings. This negative footprint illusion was as large in magnitude for the experts as it was for a group of novices without academic training in energy-related fields. We conclude that people are not immune to the negative footprint illusion even when they have the knowledge necessary to make accurate judgments.